Propionic acid accumulation in anaerobic digestion of carbohydrates: An investigation on the role of hydrogen gas - (:unkn) unknown (Elsevier Science Ltd, Exeter, United Kingdom, 1999)
This paper describes the experimental investigation into the accumulation of propionic acid under artificially lowered or elevated hydrogen gas levels. Vacuum operation at 0.13, 0.5, and 0.75 atm on the headspace of the reactors, and a selective permeable Teflon membrane placed in the liquid phase, were used to provide low hydrogen concentrations. In the elevated hydrogen concentration experiments, first, hydrogen gas (20% H2 + 80% N2) was bubbled into a batch CSTR reactor. Second, purer H2 gas (80% H2 + 20% CO2) was overpressurized at 2 atm in vials. Suspended cultures were used in all the experiments. The results have suggested no inhibition or stimulation effect by elevated or lowered hydrogen on the accumulation of propionic acid.This paper describes the experimental investigation into the accumulation of propionic acid under artificially lowered or elevated hydrogen gas levels. Vacuum operation at 0.13, 0.5, and 0.75 atm on the headspace of the reactors, and a selective permeable Teflon membrane placed in the liquid phase, were used to provide low hydrogen concentrations. In the elevated hydrogen concentration experiments, first, hydrogen gas (20% H2 + 80% N2) was bubbled into a batch CSTR reactor. Second, purer H2 gas (80% H2 + 20% CO2) was overpressurized at 2 atm in vials. Suspended cultures were used in all the experiments. The results have suggested no inhibition or stimulation effect by elevated or lowered hydrogen on the accumulation of propionic acid.
Keywords: Anaerobic; Carbohydrate; Hydrogen; Inhibition; Propionic acid; Wastewater